Brian Cherney’s String Trio: Transcendent Pedagogy and the Spiritualization of Technique - Schultz, Arlan (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2017)
Brian Cherney’s pedagogical and compositional philosophy is examined from the perspective of transcendent intention. Both in teaching composition and in his own works, Cherney emphasizes technique, attention to details, a convincing formal architecture, and the power of music to give expression to fundamental human emotions and experiences. Drawing upon the philosopher Henri Bergson’s concepts about the “nature of creative consciousness,” the author finds striking parallels between Bergson’s ideas and Cherney’s music. Analytical observations on Cherney’s String Trio are tied to the composer’s pedagogical approach, which profoundly influenced the author both as a composer and as a teacher. Cherney’s String Trio confronts the listener with a work in which the spiritual expression of a universal impermanence is manifested in the music itself in various ways that are illuminated and discussed using specific musical examples.